2018
DOI: 10.3390/nu10081099
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Protein, Leucine, Omega-3 Fatty Acids, and Vitamin D in the Prevention and Treatment of Sarcopenia and Functional Decline

Abstract: Aging is associated with sarcopenia and functional decline, leading to frailty and disability. As a modifiable risk factor, nutrition may represent a target for preventing or postponing the onset of these geriatric conditions. Among nutrients, high-quality protein, leucine, vitamin D, and omega-3 polyunsaturated fatty acids (n-3 PUFA) are of particular interest for their demonstrated effects on skeletal muscle health. This narrative review aims to examine the recent observational and interventional evidence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 127 publications
(146 reference statements)
1
73
1
4
Order By: Relevance
“…It is important to underline the role of an adequate diet and the use of dietary supplements in the 'active aging' population [45,46]. Indeed, these two interventions combined with vitamin D and amino acid supplementation and physical exercise could prevent several sequelae of the aging process including sarcopenia, as shown by several studies in the literature [47][48][49][50][51][52][53]. Finally, it has been demonstrated that there is a strong correlation between the adherence to a Mediterranean diet and a lower risk of OA manifestation, mediated by the well-known anti-inflammatory activity of fibers [54].…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%
“…It is important to underline the role of an adequate diet and the use of dietary supplements in the 'active aging' population [45,46]. Indeed, these two interventions combined with vitamin D and amino acid supplementation and physical exercise could prevent several sequelae of the aging process including sarcopenia, as shown by several studies in the literature [47][48][49][50][51][52][53]. Finally, it has been demonstrated that there is a strong correlation between the adherence to a Mediterranean diet and a lower risk of OA manifestation, mediated by the well-known anti-inflammatory activity of fibers [54].…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%
“…Further research is needed in order to establish the potential dose-dependent mechanism of PUFA when combined with other tailored strategies for the management of malnutrition, cachexia, sarcopenia and frailty in COPD. It has been suggested that medical nutrition interventions providing adequate protein, the amino acid leucine, vitamin D and PUFA may convey added benefits in the management of sarcopenia and functional decline (36).…”
Section: Multi-modal Interventions and Future Directionsmentioning
confidence: 99%
“…Tessir et al 32 demonstraram que uma ingestão inadequada de proteína, ômega 3 e vitamina D pode promover sarcopenia, com redução da massa muscular, da força muscular ou da performance física, além de diminuir mobilidade e aumentar mortalidade ou morbidade. Além disso, outro estudo recente avaliou o impacto da nutrição e do exercício na massa muscular esquelética e demonstrou que proteína, aminoácidos essenciais, vitamina D e ômega 3 atuam no processo de contração muscular, produção de energia e estímulo mitocondrial, o que melhora a utilização de gordura pelo músculo como substrato energético 33 .…”
Section: Tratamento Nutricionalunclassified